Does the trunk stability push-up provide an effective measure of upper-body function specific to male team sport athletes? - Lockie, R. G.; Callaghan, S. J.; Jordan, C. A.; Luczo, T. M.; Jeffriess, M. D. (Journal of Athletic Enhancement, 2013)
Study background: The trunk stability push-up (TSPU) is a closed-chain test that can measure upper-body functional strength, but may not relate to sport-specific performance. The bilateral medicine ball chest pass (MBCP) is a more sport-specific openchain assessment. This research investigated whether the TSPU related to bilateral MBCP to determine whether it was a valid test of team sport upper-body function.